Stop and go: Antagonistic signals in the specification of the Drosophila R7 photoreceptor viewed from an evolutionary perspective - Mavromatakis, Yannis Emmanuel (Landes Bioscience, 2012)
The Drosophila R7 photoreceptor precursor is directed to its fate by signals from adjacent cells that activate its Receptor Tyrosine Kinase (RTK) and Notch (N) signaling pathways. Counter-intuitively, the N activity both promotes and inhibits the photoreceptor fate in the R7 precursor. We offer an evolutionary perspective for this in which earlier ommatidia had fewer photoreceptors and used N to inhibit the addition of any more. When additional photoreceptors were added by evolution, an RTK signal was used to overcome the N inhibition in these cells, and these new additions potently activated N in their neighboring cells, preventing them from also responding to the RTK signal. The R7 precursor also receives this block, and requires robust RTK activation for it to become a photoreceptor. This is achieved by N transcriptionally activating a new RTK, one that is potently activated in the R7 precursor and sufficing to overcome the N inhibition. The unusually high RTK signal in R7 requires additional transduction components not needed when the signal is mild; in R7 the small GTPases Ras and Rap are both required to transduce the signal, but in other photoreceptors Ras alone suffices.